XPO1 Inhibition using Selinexor Synergizes with Chemotherapy in Acute Myeloid Leukemia by Targeting DNA Repair and Restoring Topoisomerase IIα to the Nucleus - Ranganathan, Parvathi; Kashyap, Trinayan; Yu, Xueyan; Meng, Xiaomei; Lai, Tzung-Huei; McNeil, Betina; Bhatnagar, Bhavana; Shacham, Sharon; Kauffman, Michael; Dorrance, Adrienne M.; Blum, William; Sampath, Deepa; et al. (Clinical cancer research, 2016)
Purpose: Selinexor, a selective inhibitor of XPO1, is currently being tested as single agent in clinical trials in acute myeloid leukemia (AML). However, considering the molecular complexity of AML, it is unlikely that AML can be cured with monotherapy. Therefore, we asked whether adding already established effective drugs such as topoisomerase (Topo) II inhibitors to selinexor will enhance its anti-leukemic effects in AML. Experimental Design: The efficacy of combinatorial drug treatment using Topo II inhibitors (idarubicin, daunorubicin, mitoxantrone, etoposide) and selinexor was evaluated in established cellular and animal models of AML. Results: Concomitant treatment with selinexor and Topo II inhibitors resulted in therapeutic synergy in AML cell lines and patient samples. Using a xenograft MV4-11 AML mouse model, we show that treatment with selinexor and idarubicin significantly prolongs survival of leukemic mice compared with each single therapy. Conclusions: Aberrant nuclear export and cytoplasmic localization of Topo IIα has been identified as one of the mechanisms leading to drug resistance in cancer. Here, we show that in a subset of patients with AML that express cytoplasmic Topo IIα, selinexor treatment results in nuclear retention of Topo IIα protein, resulting in increased sensitivity to idarubicin. Selinexor treatment of AML cells resulted in a c-MYC–dependent reduction of DNA damage repair genes (Rad51 and Chk1) mRNA and protein expression and subsequent inhibition of homologous recombination repair and increased sensitivity to Topo II inhibitors. The preclinical data reported here support further clinical studies using selinexor and Topo II inhibitors in combination to treat AML. Clin Cancer Res; 22(24); 6142–52. ©2016 AACR.